Elementary School Class Teacher Strategy in Instruding Ideological Values Nahdlatul Ulama – Muhammadiyyah - Lailatul Rahmi; Moh. Ferdi Hasan; Diana Monita (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research is designed to evaluate and analyze: (1) How classroom teachers formulate strategies to instill NU-Muhammadiyah ideological values in primary schools, (2) How the implementation of classroom teacher strategies in instilling NU-Muhammadiyah values in primary schools, and (3) How the evaluation of classroom teacher strategies in instilling NU-Muhammadiyah ideological values in primary schools. A qualitative approach with a multi-case study design was used in this research, and the subjects of the study were classroom teachers in NU-Muhammadiyah-based primary schools, selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document study. Data analysis was done using two models, single case analysis and cross-case analysis with spiral data analysis techniques, which include: (1) Data management, (2) Reading and coding, (3) Reduction, (4) Description, classification, and interpretation, and (5) Presentation and conclusion. The validity of the data was checked through credibility and confirmability tests. The results of this study show that: (1) The formulation of ideological strategies based on NU and Muhammadiyah values consists of three stages, namely external-internal analysis and ideological source analysis, setting vision-mission and strategic policies and philosophical-ideological values including Tauhid, Maslahat, Dakwah, Nationalism, Humanism, Modernism, Musyawarah, and Tawakkal. (2) The implementation of NU-Muhammadiyyah ideology-based strategies involves the process of program development, budgeting, and leadership, (3) The evaluation of NU-Muhammadiyyah ideology-based strategies involves the process of monitoring, clarification, performance measurement, and correction.